Students’ Opinion on the Quality of Study Programs Implemented in Latvia in the Field of Education - Davidova, Jelena; Zarina, Sandra; Ignatjeva, Svetlana; Zalitis, Ivars; Bogdane, Eva (Pedagogika, 2024)
This article examines the factors and criteria characterizing the quality of teacher study programs implemented in Latvia. In one of the universities in Latvia, the opinion of students of bachelor’s, master’s, and doctor’s level in the field of education about the quality of studies is ascertained. As a result, the most important factors affecting the quality of studies, according to the students, are collected and analysed.